PREFERENSI Nezara viridula ORDO Hemiptera PADA BEBERAPA JENIS VARIETAS KEDELAI (Glycine max. L) - Irna Syofia; Faisal Amri (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
The aim of this research was to investigate the Soyben varieties that damage inferior relative. This research utilize agglomerate Random Design (RACK) Factorial is with 2 factor those are analyzed which is N.viridula amount factor( K ), varietas's type factor (V ). Conduct that at quiz as follows for N. viridula amount( K) and varietas's type( V ) by following conduct combines: KoV1= 0 / anjasmoro, K1V1 = 3 number / anjasmoro, K2V1 = 6 number / anjasmoro, K3V1 = 9 number / anjasmoro, and KoV2= 0 / grobongan, K1V2 = 3 number / grobongan, K2V2 = 6 number / grobongan, K3V2 = 9 number / grobongan, KoV3= 0 / kaba, K1V3 = 3 number / kaba,K2V3 = 6 number / kaba, K3V3 = 9 number / kaba. Result observationaling to point out that supreme attack intensity N. Viridula available on varietas kaba which is as big as 6,17 % and bottom most on varietas anjasmoro which is as big as 5,56%. Application of N. Viridula as much 9 number evoke highest attack intensity which is as big as 11,33%. Usufruct supreme Soybean on varietas anjasmoro without application N. Viridula which is as big as 2.03 tons / ha whereas supreme result losses also on varietas anjasmoro with application N. Viridula as much 9 numberKey word: N. Viridula, attack intensity, result, soybean